Wage Inequality in East-Central Europe - Gabor Kertesi; Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2000)
The substantial rise of wage inequality in Central and Eastern Europe has attracted the attention of sociologists, concerned with social equity, and economists for whom it indicated the growing differentiation and restructuring of relative prices on the labour market. This research wanted to study wage inequalities from the second point of view by analyzing relative wages during the transition period in Hungary and Romania. In this paper we would like to discuss the policy relevance of the research, summarize the main empirical findings and draw conclusions for policy.
Keywords: 330